2009
DOI: 10.1097/mcg.0b013e318151f9d7
|View full text |Cite
|
Sign up to set email alerts
|

Gross Lower Gastrointestinal Bleeding in Patients on Anticoagulant and/or Antiplatelet Therapy

Abstract: Use of antiplatelets/anticoagulant drugs is an independent predictor of severe LGIB and is associated with adverse outcomes. Colonoscopy is required in patients who bleed while using such drugs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…by guest on May 11, 2018 http://circ.ahajournals.org/ Downloaded from with more severe bleeding (35.4% versus 55.1%, P=0.03) as defined by hemodynamic instability and the need for transfusion. 23 Our data extend this literature by quantifying the risk of UGIE, LGIE, and bleeding-related transfusions and hospitalizations associated with antiplatelets, and presents these data in the context of the way antiplatelet drugs are prescribed in this country, in dual and triple combinations, including ASA and anticoagulants.…”
Section: Discussionmentioning
confidence: 86%
“…by guest on May 11, 2018 http://circ.ahajournals.org/ Downloaded from with more severe bleeding (35.4% versus 55.1%, P=0.03) as defined by hemodynamic instability and the need for transfusion. 23 Our data extend this literature by quantifying the risk of UGIE, LGIE, and bleeding-related transfusions and hospitalizations associated with antiplatelets, and presents these data in the context of the way antiplatelet drugs are prescribed in this country, in dual and triple combinations, including ASA and anticoagulants.…”
Section: Discussionmentioning
confidence: 86%
“…60 The most common causes of upper GI blood loss in these patients are peptic ulcer disease and erosive disease of the esophagus, stomach, and duodenum, 61 whereas diverticular bleeding seems to be the most common cause of lower GIB. 62,63 In 1 retrospective series of 52 patients, correction of the INR to 1.5 to 2.5 allowed successful endoscopic diagnosis and therapy at rates comparable with those achieved in nonanticoagulated patients. 4 In a recently reported large series in which 95% of patients had INRs between 1.3 and 2.7, endoscopic therapy achieved initial success in 94.7% (233/246) of patients by using a variety of hemostatic techniques including injection therapy, heater probe, and hemoclips.…”
Section: Efficacy Of Endoscopic Therapy In Patients Actively Taking Amentioning
confidence: 79%
“…Owing to the small number of patients, it cannot be safely concluded that the medications had no asscoiation with lower GI bleeding. Nonetheless, care should be taken for the management of patients with lower GI bleeding when they are prescribed with NSAIDs and anticoagulants (21).…”
Section: Discussionmentioning
confidence: 99%